Two articles: The future of cancer therapy and The function of lipin in obesity and lipodystrophy - Lowthers, Erica L.; McMaster, Christopher R. (DALHOUSIE MEDICAL JOURNAL, 2006)
The future of cancer therapy, Erica L. Lowthers American Association of Cancer Research meeting notes, Washington, April 2006 The function of lipin in obesity and lipodystrophy, Christopher R. McMaster Experimental Biology meeting notes, San Francisco, April 2006